ESCRITA DE AUTORIA FEMININA E A (DES) CONSTRUÇÃO DA IDENTIDADE NO ROMANCE PÉROLAS ABSOLUTAS DE HELOISA SEIXAS - Oliveira, Nayara de (2015)
The research analyses the feminine representations in the romance Absolute Pearls of the contemporary writer Heloisa Seixas. Based on feminist theories dedicated to question the binary view of the gender, as well as the contributions of Cultural Studies, which debate the question of identity in contemporary society, our analysis reflects the (de)construction) of the feminine identity (identities) in the selected romance, addressing, especially, in the relation between sexuality, myth and body present in the romance, the new settings of feminine identity in the contemporary literature written by women. By understanding the female inclusion in the literature universe in its historical and social dimension, it is possible to see that from the earliest writers, there was the feminine aspiration for no longer just to be represented, to finally be able to express the varied ways in which women see themselves, in order to break with the feminine models found in the works that compose the literature canon, which have feminine identities based on traditional archetypes, responsible for crystallize female images in the collective imagination according to androcentric vision. The romance of Heloisa Seixas renews the myth of the androgyne to flirt with the idea of seeking the "other half", separated souls predestined to meet, that usually the literature tradition is between a man and a woman, but in the Pearl Absolute occurs between two female characters, which surpass the condition of rivals and develop a homoaffective relationship. If the literary tradition, consisted of works by male authors, brings female characters built based on traditional archetypes, being appealing the denial of sexuality and woman`s right to her own body, or even, exploring this theme in order to match the male desire, the literature of female author is presented as escape route to such standards, as found in the works of contemporary writers feminine representations that transgress the traditional images to realize the plurality of meanings that the feminine identity can assume.